EFEKTIVITAS PEMBERIAN CITRUS BAKING SODATERHADAP PENGHILANGAN STAIN PADA PRIA PEROKOK USIA 20-55 TAHUN DI KELURAHAN TANJUNGBALAI KOTA II, Lk. III KECAMATAN TANJUNGBALAI SELATAN - Aritonang, Intan; Sinulingga, Devi Ray Syahfitri (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2019)
Citrus and baking soda are kitchen ingredients that are often found in everyday life, have ingredients thatcan blot stains on teeth, especially stains of cigarettes or stains that can affect the color of teeth. This type ofresearch is analytic research with a quasi experiment method which aims to determine the effectiveness ofgiving citrus with baking soda to stain removal in smokers aged 20-55 years Tanjungbalai Kota II Village,Lk. III, South Tanjungbalai District with a sample of 30 people. The results showed that the average stainstate before being given was given citrus gel with baking soda to smokers aged 20-55 years in Lk. IIIKelurahan Tanjungbalai Kota II, Kecamatan Tanjungbalai Selatan, lobene intensity of 0.879, with lobenearea of 1.084, and combined lobene of 0.081. Meanwhile for stain conditions after being given citrus gelwith baking soda for smokers aged 20-55 years at Lk. III Kelurahan Tanjungbalai, Kecamatan TanjungbalaiSelatan, lobene intensity of 0.408, lobene area of 0.493, combined lobene of 0.037. That it is effective to givecitrus baking soda gel to stain removal using the dependent t-test with a value of p (0,000) <? (0.05). Thisstudy concluded that the effectiveness of giving citrus with baking soda to stain removal. It is hoped that thecommunity will use the gel as recommended.